Relações filogenéticas em Oecomys Thomas, 1906, com ênfase em sistemática e diversificação do complexo Oecomys catherinae Thomas, 1909 (Rodentia, Sigmodontinae) - Silva, Juliane Saldanha da (2020)
The arboreal rat Oecomys Thomas, 1906 are widely distributed in Brazilian biomes, with the greatest diversity reported for the Amazonia region. Currently, 18 species are recognized. However, the real diversity and species boundaries in the genus remains uncertain., and the interspecific relationships still poorly known. The great diversity of Oecomys is reported in studies about species complex, with lineages that may represent new species. The aim of this study is to evaluate the taxonomic diversity and phylogenetic relationships of Oecomys species, with emphasis on the most diverse species complex – Oecomys catherinae – which is widely distributed in Brazilian biomes. We performed phylogenetic analyses based on mitochondrial and nuclear marker to elucidate the diversity and relationships between Oecomys species of Tapajós basin and the role of Amazonian rivers in the species distribution. For the O. catherinae complex, we performed molecular analyses of species delimitation, and morphological and morphometric analyses. In addition, we used a genomic representation of ddRADseq to evaluate the phylogenetic relationships and diversification of the lineages of the complex. Our phylogenetic hypotheses for Oecomys genus reveal great species diversity for the Tapajós basin, with the distribution of some species shaped by the Tapajós river, but the Teles Pires river does not act as a barrier to gene flow for other species. The species delimitation, morphology and morphometric analyses indicate the existence of a new species of the O. catherinae complex for this region, described in this study. The genomic approach reveals the divergences and diversity between the other lineages of the O. catherinae complex, with evidence of two distinct species in Amazonia, and cryptic species occurring in the Atlantic Forest and Cerrado biomes. The diversifications between lineages of the complex were estimated for the Pleistocene, largely shaped by the refuges and glaciations of this period.